Subungual exostosis of the thumb - first case report in youngest age - Gupta Sanjeev; Mittal Amit; Gupta Sunita; Mahendra Aneet; Dhull Anil (Wolters Kluwer Medknow Publications, 2009)
Subungual exostosis (SE) is a benign osteocartilaginous tumor of the ungual apparatus, particularly of the toes. It affects both sexes equally, more frequently in the second and third decades of life. The present case highlights this entity (SE) in a six and half year old female child affecting the terminal phalanx of the right thumb. She presented to us with gradually enlarging, painless, subungual hard nodule on the right thumb. Roentogram of the hand showed bony outgrowth arising from the terminal phalanx of right thumb. Lesion was excised and sent for histopathological examination. Histology showed evidence of SE. No recurrence at postoperated site was seen till eight months of follow-up.